Effect of lactose intolerance severity on food intake and quality of life in adults with lactose intolerance in Turkey - Gökçen Garipoğlu; Nesli Ersoy; Mustafa Gülşen; Taner Özgürtaş (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - Lactose intolerance is lactose digestive disorder due to lactase enzyme deficiency. This can affect the quality of life by restricting the intake of certain foods. The aim of this study is to show the lactose intolerance to the restriction in food intake and quality of life. Design/methodology/approach - This study was conducted with adults aged 18-60 years. A survey was used to gather information on the demographic characteristics of the patients and their symptoms related to lactose intolerance. In addition, the Visual Analog Scale was administered to identify common symptoms and the World Health Organization Quality of Life (WHOQOL)-Bref Quality of Life Scale to determine their quality of life. Findings - The average quality of life subscale scores was 56.25 ± 14.06 for physical, 58.29 ± 11.72 for mental, 63.28 ± 21.35 for social and 62.36 ± 16.37 for environmental. When VAS scores obtained for the common digestive system symptoms in lactose intolerance were compared with Quality of Life scores; it was found that physical life quality scores decreased (r = −0.239, p = 0.030) as the complaints of diarrhea increased and physical and environmental life quality decreased (r = −0.316, p = 0.004/r = −0.277, p = 0.012, respectively) as abdominal pain increased. Originality/value - People reduce dairy consumption due to digestive system complaints. Therefore, it is important to inform the people about the effects of lactose intolerance because discomfort caused by intolerance can affect nutrient intake and lower the quality of life.